A new analytical identification approach to the tooth contact points considering misalignments for spiral bevel or hypoid gears. (March 2018) - He, Di; Ding, Han; Tang, Jinyuan
Highlights: The accurate initial values are determined by considering the misalignment condition including the assembly distance and the instantaneous transmission ratio. A novel approach to tooth contact analysis (TCA) considering the misalignment by computing the geometric kinematic transformation. A self-adaptive trust region algorithm based on a conic model is employed in the identification of the accurate initial values. A multi-step integrated analytical computation is proposed to identify the tooth contact points especially the initial contact point. Abstract: With the increasing demands of low noise and high strength from industry applications for spiral bevel and hypoid gears, it is significant to consider the tooth contact performances, which dependents on tooth contact analysis (TCA) technology. The initial contact point, especially its initial value problem, is always of a great influence on TCA results. Furthermore, misalignments condition in the actual manufacturing is an important factor affecting tooth contact performance. A new multi-step integrated analytical identification approach is proposed to identify the initial contact point considering misalignments. First, the initial contact points on gear and pinion are identified to solve for the accurate initial values of TCA by considering the misalignments. In the consideration of misalignments, the assembly distance and the instantaneous transmission ratio are set the two constraints on solution of TCA. Then, the geometric kinematic transformation relation in tooth contact process is investigated to identify the initial contact point. Finally, a conic self-adaptive trust region algorithm is employed to get the contact points. The numerical test is given to validate the proposed methodology.